The Stokes’ Theorem - Ghawsi, Ghiyasuddin (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Stokes theorem for the first presented in 1854 as a research question in Cambridge University of England by George Gabriel Stokes Irish mathematician (1819-1903). Stokes theorem is the generalized form of Green’s theorem, since Green’s theorem connects double integral of plane region D to curve line integral which bounded this surface ...